Landlocked Atlantic salmon Salmo salar L. and trout Salmo trutta L. in the regulated River Klarälven, Sweden : Implications for conservation and management - Norrgård, Johnny R (Avdelningen för biologi, 2011)
Conservation and management of migratory salmonids requires an understanding of their ecology at multiple scales, and a holistic view, including assessment of historical and present anthropogenic impacts. In the regulated River Klarälven, with 11 hydropower dams, populations of landlocked Atlantic salmon Salmo salar and migratory brown trout Salmo trutta have declined due to human activities. Maintaining viable populations of salmon in the River Klarälven has high priority, given there are fewer than 10 native stocks of landlocked salmon in Europe. To date, natural smolt production has been maintained by collecting and transporting spawners past eight hydroelectric plants in the river, where they are released to spawn. No functioning fish passage facilities are available that allow the fish to return to the lake. To evaluate the situation for landlocked salmon and migratory trout in Lake Vänern and the River Klarälven, an analysis of catch and river return data, based on data sets covering time periods from 15 to 200 years, was performed. In addition, the loss rates and behavior of downstream-migrating wild salmon smolts as they swam past eight power stations in the regulated River Klarälven was quantified. For the migration study, wild salmon smolts were tagged with acoustic transmitters, and the smolts were monitored as they swam along a 180 km long river segment, including eight dams, with regulated and unregulated stretches. The loss due to HEP passages was estimated to be 76%, which contrasts with the 8% loss along unregulated control stretches. Kaplan-Meier estimations showed that only 16% of the smolts passed all eight dams. Migration speed was 83% lower along regulated stretches than along unregulated stretches, and migration speed at regulated stretches was dependent on fish size, with large fish moving slower than small fish. The analysis of historical data showed that annual returns of wild salmon are less than 3% of what they were at the beginning of the 19th century. Returns of wild trout are even ...